2020
DOI: 10.1155/2020/1320274
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Antimicrobial and Catalytic Properties of Gold Nanoparticles Greenly Synthesized by Cryptolepis buchanani Roem. and Schult Extract

Abstract: A green, simple, and rapid synthesis of gold nanoparticles using plant extract, Cryptolepis buchanani Roem. and Schult, and their applications are first described in this paper. The formation of gold nanoparticles was visually observed by the appearance of a ruby red color, which was further indicated by an absorption peak at 530 nm in UV-Vis spectroscopy. Optimization of reaction parameters for the gold nanoparticles was also investigated. Various analytical techniques were employed as part of the process of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…Figure 5 represents the UV-Visible absorbance spectra of the Au NPs which gives maximum absorption at around 550-560 nm. These results of UV-Visible absorbance spectra of Au NPs are in good agreement with available literature (Wongyai et al, 2020). Peak broadening and red shift were observed and noted in alkaline medium (Islam et al, 2019).…”
Section: Ftir Xrd and Uv-visible Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…Figure 5 represents the UV-Visible absorbance spectra of the Au NPs which gives maximum absorption at around 550-560 nm. These results of UV-Visible absorbance spectra of Au NPs are in good agreement with available literature (Wongyai et al, 2020). Peak broadening and red shift were observed and noted in alkaline medium (Islam et al, 2019).…”
Section: Ftir Xrd and Uv-visible Analysissupporting
confidence: 91%
“…Various physical (Mafuné et al, 2002) and chemical methods (Oliveira et al, 2020;Hussain et al, 2020) are reported for the synthesis of Au NPs. The physical methods has a high production cost as it requires high energy and pressure during the synthesis procedure (Wongyai et al, 2020). In chemical methods, toxic compounds as a reducing agent are used to synthesize NPs which are not appropriate for long-term environmental sustainability, toxic to human health and environment and produce toxic hazardous byproducts in large quantity (Folorunso et al, 2019;Dzimitrowicz et al, 2019;Islam et al, 2019), and greatly limits their applications in the fields of biomedical, especially in clinical purposes (Kunoh et al, 2018).…”
Section: Synthesis Of Au Npsmentioning
confidence: 99%
“…Very recently, Akintelu et al [52] reported the synthesis of spherical and stable gold nanoparticles using pulp of Garcina kola at pH 7. Similarly, Wongyai et al [53] studied the biosynthesis of AuNPs using the aqueous extract of Cryptolepis buchanani Roem to produce highly stable, small-sized AuNPs with a uniform spherical shape at pH 7. The stability confirmed by the zeta potential analysis was −30.28 mV.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…AuNPs are used as drug carrier/delivery, bioimaging, contrast, photothermal, and anti-angiogenic agents [ 45 , 46 ]. AuNPs were investigated for antibacterial activity and found to display an effective antibacterial effect against gram-positive and gram-negative bacterial strains [ 47 , 48 , 49 , 50 ]. AuNPs can ferry and deliver hydrophobic and hydrophilic drugs, peptides, antibodies, and small molecule drugs to the targeted tumour site with no toxic effects on normal or surrounding tissues [ 51 ].…”
Section: Mnps and Their Applicationmentioning
confidence: 99%